2022
DOI: 10.3329/ijarit.v11i2.57261
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum irrigation scheduling for sorghum in Benna-Tsemay Woreda, Southern Ethiopia

Abstract: Scarcity of water is the most severe constraint for sustainable development of agriculture in arid and semi-arid areas. Hence, novel irrigation water application systems need to be developed so that high crop yield and water productivity per unit of land can be increased. Thus, the field experiment was conducted with the objective of determining the effect of different soil moisture depletion levels on yield and water use efficiency of sorghum crop in Benna-Tsemay woreda at Enchete kebele, Southern Ethiopia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The average pH of the trial location was determined to be 7.83 shown in Table 3, almost alkaline (Lebiso & Mada, 2022). The result of pH of study area soil was within the acceptable range for onions, as stated by (Olani & Fikre, 2010).…”
Section: The Chemical Properties Of Soilsupporting
confidence: 59%
See 1 more Smart Citation
“…The average pH of the trial location was determined to be 7.83 shown in Table 3, almost alkaline (Lebiso & Mada, 2022). The result of pH of study area soil was within the acceptable range for onions, as stated by (Olani & Fikre, 2010).…”
Section: The Chemical Properties Of Soilsupporting
confidence: 59%
“…The soil particle size distribution at the experimental site is shown in Table 1. The laboratory analysis revealed that the soil of the experimental field has a uniform texture with an average composition of sand, silt, and clay content of 41.5%, 24.9%, and 33.6%, respectively according to (Lebiso & Mada, 2022). As a result, the soil of the experimental field was classified as loam in texture by the USDA.…”
Section: Soil Physical Propertiesmentioning
confidence: 99%